The EFFECTIVENESS OF THE RAPID EMERGENCY MEDICINE SCORE (REMS) TRIAGE MODEL IN DETERMINING MORTALITY RISK IN DISASTER AREAS: A Literature Review - BASHOR, FURQON ABDULLAH; Rahmadinie, Amalia (Journal of Diverse Medical Research: Medicosphere, 2025)
Indonesia is one of the countries with a high risk of natural disasters with a total of 20,380 cases between 2020-2024. The high number of disasters that occur will have an impact on the high number of casualties that must be handled by medical personnel. In the event of a disaster, the number of health workers is often less than the need to cause an increase in the mortality rate of victims, therefore as an effort to increase the efficiency of the number of health workers to provide treatment, it is necessary to apply triage, one of which is the Rapid Emergency Medicine Score (REMS) triage model. The purpose of writing this article is to determine the effectiveness of triage with the REMS model used by medical personnel and volunteers in disaster areas on disaster victims. The method used is a literature review taken from several sources with a limit of 2019- 2024. From the literature review, it is found that the application of the REMS triage model has proven effective during disasters. As during the Covid 19 pandemic, this is because the REMS triage method is simple and fast; flexible and has good prognostic value; and uses Vital Signs (TTV) parameters so that it can be applied to various situations and conditions. REMS is an effective triage model for non-trauma disaster victims.